Empowerment of Elementary School Students Through Clean and Healthy Living Behavior (PHBS) Education in Preventing Diarrhea in Students of SDN 26 Galala Village, Oba Utara District, Tidore Islands City - Ismawanti Sawedi; Nursia Aja; Norma B. Toduho; Diah Ariana; Maya Sari Soamole (International Journal Of Community Service, 2026)
This activity aims to empower students of SDN 26 Galala Village through education on Clean and Healthy Living Behavior (PHBS) in an effort to prevent diarrhea. The program was implemented on August 11, 2025, involving 52 students from grades 1, 2, and 4. The method used was empowering elementary school students through education on clean and healthy living behavior in order to prevent diarrhea, such as washing hands with soap and maintaining personal and environmental hygiene to avoid and prevent diarrhea. The results of the activity showed an increase in students' knowledge, attitudes, and skills in implementing PHBS and understanding the initial treatment of diarrhea. Support from the school showed the success of this program in fostering a culture of healthy living in the elementary education environment. Overall, this activity effectively increased students' awareness as agents of change in healthy behavior to prevent diarrhea. Observation results show an increase in students' knowledge and awareness of the importance of clean and healthy living. Students are able to explain how to wash their hands properly and understand its relationship to disease prevention. So teachers also support this activity because it is considered to strengthen a healthy culture at elementary school SDN 26 Galala Village, Oba Utara District, Tidore Islands City. The impact is seen from changes in student behavior who are more concerned about cleanliness. This activity proves the active role of PBL II students in empowering students as agents of change in healthy behavior.